Reach and Weaknesses of Asset Forfeiture Policy in Corruption Crimes in Indonesia - Arizon Mega Jaya; Maroni Maroni; Ahmad Irzal Fardiansyah; Muhammad Akib (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2025)
This article discusses the reach and weaknesses of the policy of asset forfeiture of corruption crimes in Indonesia. The main problem lies in the lack of optimal ability of the legal system to change the normative basis of asset confiscation into real state loss recovery. This research uses normative juridical methods with legislative, conceptual, and institutional approaches. The analysis is directed at the ability of asset forfeiture policies to reach hidden assets, assets transferred through third parties or nominees, assets located abroad, and assets that have been disguised through money laundering crimes. The results of the study show that the asset forfeiture policy in Indonesia has a normative reach through the Law on the Eradication of Corruption Crimes, the Money Laundering Law, mutual legal assistance mechanisms, and international cooperation. However, its effectiveness is still limited by the dominance of the conviction-based confiscation approach, the lack of clarity of proportionality parameters, weak beneficial ownership arrangements, the lack of strong third-party protection, limited asset tracing, the suboptimal execution of replacement money, and institutional coordination that has not been integrated. This article confirms that the renewal of the asset forfeiture policy needs to be directed towards a more integrated model, oriented towards asset recovery, and still guaranteeing the protection of rights within the principle of the rule of law.